2018
DOI: 10.1093/nar/gky561
|View full text |Cite
|
Sign up to set email alerts
|

A survey of recent unusual high-resolution DNA structures provoked by mismatches, repeats and ligand binding

Abstract: The structure of the DNA duplex is arguably one of the most important biological structures elucidated in modern history. DNA duplex structure is closely associated with essential biological functions such as DNA replication and RNA transcription. In addition to the classical A-, B- and Z-DNA conformations, DNA duplexes are capable of assuming a variety of alternative conformations depending on the sequence and environmental context. A considerable number of these unusual DNA duplex structures have been identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 121 publications
2
26
0
Order By: Relevance
“…Although these defects are generally associated with increased DNA bendability (see e.g. Vafabakhsh and Ha, 2012; Satange et al , 2018), this might not always be the case, as suggested by recent studies (Rossetti et al ., 2015; Jeong and Kim, 2019). Using MD simulations and nuclear magnetic resonance experiments, Orozco, Gonzalez, and coworkers performed a systematic study of the effect of mismatches on DNA flexibility (Rossetti et al ., 2015).…”
Section: Chemical Modifications and Dna Mechanicsmentioning
confidence: 95%
“…Although these defects are generally associated with increased DNA bendability (see e.g. Vafabakhsh and Ha, 2012; Satange et al , 2018), this might not always be the case, as suggested by recent studies (Rossetti et al ., 2015; Jeong and Kim, 2019). Using MD simulations and nuclear magnetic resonance experiments, Orozco, Gonzalez, and coworkers performed a systematic study of the effect of mismatches on DNA flexibility (Rossetti et al ., 2015).…”
Section: Chemical Modifications and Dna Mechanicsmentioning
confidence: 95%
“…The small molecules that recognize these mismatched DNA duplexes can induce various degrees of structural deformations, with many having pharmaceutical and/or diagnostic potential (10,11). The presence of unstable mismatches in DNA structures may cause base flipping into extrahelical positions, which itself is an important phenomenon observed upon small molecule ligand binding to DNA duplexes (12–14).…”
Section: Introductionmentioning
confidence: 99%
“…How to construct and describe mismatched base-pairing interactions in structural details is a key issue for understanding the mechanism of the formation of non–B-DNA and finding effective ways to treat some genetic diseases. Numerous studies have shown that many small-molecule intercalators with pharmaceutical and/or diagnostic potential ( Satange et al, 2018 ; Pages et al, 2019 ) can recognize mismatched DNA or RNA duplexes and induce various degrees of structural deformations. The existence of unstable mismatches in nucleic acid sequences may cause nucleobases flipping into additional helical positions, which itself is a significant phenomenon observed during the binding of small-molecule ligands to DNA or RNA duplexes ( Jourdan et al, 2012 ; Tseng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%